Edukasi Gemar Menabung Sejak Dini Melalui Kegiatan Mewarnai Celengan di SD Negeri 1 Gelam - Adynda Dara Meylia; Novisah; Nurhasbiyah Maya Iswanti; Siti Maimunah (INDO PUBLISHING, 2025)
The habit of saving from an early age is a crucial strategy in fostering responsible financial character in children. The consumptive behavior among elementary school students indicates that most children do not yet understand the importance of setting aside pocket money for long-term needs. The